2021
DOI: 10.3390/antiox10122001
|View full text |Cite
|
Sign up to set email alerts
|

The Synbiotic Combination of Akkermansia muciniphila and Quercetin Ameliorates Early Obesity and NAFLD through Gut Microbiota Reshaping and Bile Acid Metabolism Modulation

Abstract: Gut microbiota plays a key role in obesity and non-alcoholic fatty liver disease (NAFLD), so synbiotics could be a therapeutic alternative. We aim to evaluate a nutritional intervention together with the administration of the bacteria Akkermansia muciniphila and the antioxidant quercetin in an in vivo model of early obesity and NAFLD. 21-day-old rats were fed with control or high-fat diet for six weeks. Then, all animals received control diet supplemented with/without quercetin and/or A. muciniphila for three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 77 publications
2
43
1
Order By: Relevance
“…54 In addition, the CA/(glychocholic acid (GCA) + taurocholic acid (TCA) ratio was positively correlated with A. muciniphila, which may be related to BSHs. 54 Lactis 420™ (B420) was administered alone and in combination with prebiotics. The results showed changes in microbial and plasma BAs.…”
Section: Bile Acidsmentioning
confidence: 98%
See 2 more Smart Citations
“…54 In addition, the CA/(glychocholic acid (GCA) + taurocholic acid (TCA) ratio was positively correlated with A. muciniphila, which may be related to BSHs. 54 Lactis 420™ (B420) was administered alone and in combination with prebiotics. The results showed changes in microbial and plasma BAs.…”
Section: Bile Acidsmentioning
confidence: 98%
“…After feeding A. muciniphila and quercetin, total plasma BAs increased, and secondary BAs increased overall, especially ωMCA and UDCA. The combination therapy reduced the levels of fasting blood glucose and plasma insulin and prevented obesity and inflammation 54 . In addition, the CA/(glychocholic acid (GCA) + taurocholic acid (TCA) ratio was positively correlated with A. muciniphila , which may be related to BSHs 54 .…”
Section: Beneficial Metabolites Of Gut Microbiotamentioning
confidence: 99%
See 1 more Smart Citation
“…Two double-blind, placebo-controlled clinical trials report that the mixture of Bifidobacterium bifidum BB-02 , Bifidobacterium lactis BL-01 , and inulin, as well as mixture of Lactobacillus acidophilus NCFM and lactitol can increase the growth of Bifidobacteria and Lactobacilli [ 213 , 215 ]; in addition, another clinical trial shows that the combination of Bifidobacterium longum and inulin increased the number of Actinobacteria and Firmicutes , and decreased Proteobacteria [ 214 ]. Interestingly, Marìa Juàrez-Fernàndez et al observed the beneficial effect of the symbiotic combination of the NGP A. muciniphila and quercetin on NAFLD, by modulating GM composition and bile acid metabolism [ 216 ].…”
Section: Other Therapeutic Optionsmentioning
confidence: 99%
“…Obesity-attributable illnesses, such as cardiovascular disease have contributed to more than two-thirds of deaths globally, according to data from the Global Burden of Disease study ( 2 ). One of the underlying mechanisms contributing to obesity-related diseases is the development of systemic low-grade inflammation derived from adipose tissue ( 3 , 4 ). While chronic inflammation is often associated with increased oxidative stress ( 5 ), the literature has previously reported the role of oxidative stress in the pathogenesis of obesity-related diseases ( 6 ).…”
Section: Introductionmentioning
confidence: 99%